INFLUENCE OF TRIGONELLA FOENUM GRAECUM (FENUGREEK) IN ALLOXAN INDUCED DIABETIC RATS - A. RAJARAJESWARI; P. VIJAYALAKSHM; A. MOHAMED SADIQ (The Bioscan, 2012)
The present study was used to investigate the antidiabetic activity of trigonella foenum graecum in alloxan induced diabetic rats. The effect observed were compared with a known antidiabetic agent glibenclamide. In active pancreatic damage induced by alloxan (i.p.75mg/kg b.w), fenugreek seed aqueous extract (1300 mg/kg b.w) and ethanol extract (1g/kg b.w) adminstration significantly reduced the elevated level of blood glucose and increased the levels of serum insulin. It decreases the elevated levels of cholesterol, triglycerides, urea, uric acid, creatinine, glycosylated Hb, and increases the decreased levels of liver glycogen and protein. Also the histological examination of pancreas supported the antidiabetic effect of fenugreek.It is concluded that the aqueous and ethanol extract of fenugreek could act and possess good antidiabetic activity. Further Trigonella foenum graecum aqueous extract shows more significant results than Trigonella foenum graecum ethanol extract.